Animal Models of Rheumatoid Arthritis (I): Pristane-Induced Arthritis in the Rat - Tuncel, Jonatan; Haag, Sabrina; Hoffmann, Markus H.; Yau, Anthony C. Y.; Hultqvist, Malin; Olofsson, Peter; Bäcklund, Johan; Nandakumar, Kutty Selva; Weidner, Daniela; Fischer, Anita; Leichsenring, Anna; Lange, Franziska; et al. (PLOS ONE, 2016)
Background To facilitate the development of therapies for rheumatoid arthritis (RA), the Innovative Medicines Initiative BTCure has combined the experience from several laboratories worldwide to establish a series of protocols for different animal models of arthritis that reflect the pathogenesis of RA. Here, we describe chronic pristane-induced arthritis (PIA) model in DA rats, and provide detailed instructions to set up and evaluate the model and for reporting data. Methods We optimized dose of pristane and immunization procedures and determined the effect of age, gender, and housing conditions. We further assessed cage-effects, reproducibility, and frequency of chronic arthritis, disease markers, and efficacy of standard and novel therapies. Results Out of 271 rats, 99.6% developed arthritis after pristane-administration. Mean values for day of onset, day of maximum arthritis severity and maximum clinical scores were 11.8±2.0 days, 20.3±5.1 days and 34.2±11 points on a 60-point scale, respectively. The mean frequency of chronic arthritis was 86% but approached 100% in long-term experiments over 110 days. Pristane was arthritogenic even at 5 microliters dose but needed to be administrated intradermally to induce robust disease with minimal variation. The development of arthritis was age-dependent but independent of gender and whether the rats were housed in conventional or barrier facilities. PIA correlated well with weight loss and acute phase reactants, and was ameliorated by etanercept, dexamethasone, cyclosporine A and fingolimod treatment. Conclusions PIA has high incidence and excellent reproducibility. The chronic relapsing-remitting disease and limited systemic manifestations make it more suitable than adjuvant arthritis for long-term studies of joint-inflammation and screening and validation of new therapeutics.